Stigma among Singaporean youth: a cross-sectional study on adolescent attitudes towards serious mental illness and social tolerance in a multiethnic population - Pang, Shirlene (BMJ Open, 2017)
OBJECTIVES: Stigma against mental illnesses is one of the significant obstacles faced by mental health service users and providers. It can develop at a young age and is also influenced by culture. Youths in Southeast Asian countries are under-represented in mental health research, thus this study aims to explore the dimensions of stigma and social tolerance and examine its correlates in the younger, multiethnic population of Singapore. DESIGN: An online survey collected data with sociodemographic questions, the Attitudes Towards Serious Mental Illness (Adolescent version) Scale, Social Tolerance Scale and an open-text question on words or phrases participants associated with the term ‘mental illness’. Principal component analysis and multiple regression models were conducted to investigate the factor structure of the attitudes and social tolerance scales and their sociodemographic correlates. PARTICIPANTS: Participants included 940 youths aged 14–18 years old who were residing in Singapore at the time of the survey and were recruited through local schools. RESULTS: About a quarter of the students (22.6%) reported participating in mental health awareness campaigns while nearly half (44.5%) associated pejorative words and phrases with the term mental illness. The Attitudes Towards Serious Mental Illness (Adolescent version) Scale yielded five factors while the Social Tolerance Scale yielded two. Ethnicity, gender and nationality were significantly correlated with factors of both scales. Chinese youths showed higher sense of ’physical threat' and lower ’social tolerance' than those of other ethnicities. Females showed more ’wishful thinking', ’social concern' and ’social responsibility' towards the mentally ill than males. CONCLUSIONS: The dimensions of stigma and social tolerance are different in Asian cultures compared with Western cultures. Sociodemographic differences in attitudes towards the mentally ill were found among youths living in Singapore. Misconceptions and negative attitudes towards mental illness are common, demonstrating a clear need for effective stigma reduction campaigns.